(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
This article analyzes the ecological and technical aspects of the Setapret PFF substance in modern textile industry. Setapret PFF is a fluorocarbon-free water-repellent finishing agent that meets international environmental standards such as OEKO-TEX® Standard 100, ZDHC, and Bluesign. The study covers its application areas, technological parameters, and environmental safety.